Reduced intensity VEPEMB regimen compared with standard ABVD in elderly Hodgkin lymphoma patients: results from a randomized trial on behalf of the Fondazione Italiana Linfomi (FIL). (13th January 2016) - Zallio, Francesco; Tamiazzo, Stefania; Monagheddu, Chiara; Merli, Francesco; Ilariucci, Fiorella; Stelitano, Caterina; Liberati, Anna Marina; Mannina, Donato; Vitolo, Umberto; Angelucci, Emanuele; Rota Scalabrini, Delia; Vallisa, Daniele; et al.
Summary: Survival rates for elderly Hodgkin Lymphoma (HL) have not improved substantially in recent years, mainly because of a lack of prospective randomized studies, due to difficulties in enrolling patients. Between 2002 and 2006, 54 untreated HL patients, aged between 65 and 80 years and considered 'non‐frail' according to a comprehensive geriatric evaluation, were enrolled into a phase III randomized trial to compare a reduced‐intensity regimen (vinblastine, cyclophosphamide, procarbazine, prednisone, etoposide, mitoxantrone, bleomycin; VEPEMB) with standard ABVD (adriamycin, bleomycin, vinblastine, dacarbazine). Primary endpoint was progression‐free survival (PFS). Seventeen patients were in early stage (I‐IIA), while 37 were advanced stage. Median age was 72 years and median follow‐up was 76 months. Five‐year PFS rates were 48% vs. 70% [adjusted Hazard ratio (HR) = 2·19, 95% confidence interval (CI) = 0·94–5·10, P  = 0·068] and 5‐year overall survival (OS) rates were 63% vs. 77% (adjusted HR = 1·67, 95% CI = 0·69–4·03, P  = 0·254) for VEPEMB compared to ABVD. Overall treatment‐related mortality was 4%. World Health Organization grade 4 cardiac and lung toxicity occurred in four patients treated with ABVD versus no cases in the VEPEMB arm. Standard ABVD regimen resulted in better PFS and OS than the VEPEMB, although the differences were not statistically significant. The low toxicity of both treatments was probably attributable to stringent selection of patients based on a Comprehensive Geriatric Assessment that excluded frail patients.